A DNA metabarcoding approach for recovering plankton communities from archived samples fixed in formalin - Shiozaki, Takuhei; Itoh, Fumihiro; Hirose, Yuu; Onodera, Jonaotaro; Kuwata, Akira; Harada, Naomi (PloS one, 2021)
Plankton samples have been routinely collected and preserved in formalin in many laboratories and museums for more than 100 years. Recently, attention has turned to use DNA information from formalin-fixed samples to examine changes in plankton diversity over time. However, no molecular ecological studies have evaluated the impact of formalin fixation on the genetic composition of the plankton community structure. Here, we developed a method for extracting DNA from archived formalin-preserved plankton samples to determine their community structure by a DNA metabarcoding approach. We found that a lysis solution consisting of borate-NaOH buffer (pH 11) with SDS and proteinase K effectively cleaved the cross-link formed by formalin fixation. DNA was extracted from samples preserved for decades in formalin, and the diatom community of the extracted DNA was in good agreement with the microscopy analysis. Furthermore, we stored a plankton sample for 1.5 years and demonstrated that 18S rRNA gene community structures did not change significantly from non-formalin-fixed, time-zero samples. These results indicate that our method can be used to describe the original community structure of plankton archived in formalin for years. Our approach will be useful for examining the long-term variation of plankton diversity by metabarcoding analysis of 18S rRNA gene community structure.